On the pragmatic and epistemic virtues of inference to the best explanation. - Pettigrew, Richard (Synthese, 2021)
In a series of papers over the past twenty years, and in a new book, Igor Douven (sometimes in collaboration with Sylvia Wenmackers) has argued that Bayesians are too quick to reject versions of inference to the best explanation that cannot be accommodated within their framework. In this paper, I survey their worries and attempt to answer them using a series of pragmatic and purely epistemic arguments that I take to show that Bayes' Rule really is the only rational way to respond to your evidence.